MR neurography biomarkers to characterize peripheral neuropathy in AL amyloidosis. (14th August 2018) - Kollmer, Jennifer; Weiler, Markus; Purrucker, Jan; Heiland, Sabine; Schönland, Stefan O.; Hund, Ernst; Kimmich, Christoph; Hayes, John M.; Hilgenfeld, Tim; Pham, Mirko; Bendszus, Martin; Hegenbart, Ute
Abstract : Objective: To detect, localize, and quantify peripheral nerve lesions in amyloid light chain (AL) amyloidosis by magnetic resonance neurography (MRN) in correlation with clinical and electrophysiologic findings. Methods: We prospectively examined 20 patients with AL-polyneuropathy (PNP) and 25 age- and sex-matched healthy volunteers. After detailed neurologic and electrophysiologic testing, the patient group was subdivided into mild and moderate PNP. MRN in a 3.0 tesla scanner with anatomical coverage from the lumbosacral plexus and proximal thigh down to the tibiotalar joint was performed by using T2-weighted and dual-echo 2-dimensional sequences with spectral fat saturation and a 3-dimensional, T2-weighted inversion recovery sequence. Besides evaluation of nerve T2-weighted signal, detailed quantification of nerve injury by morphometric (nerve caliber) and microstructural MRN markers (proton spin density, T2 relaxation time) was conducted. Results: Nerve T2-weighted signal increase correlated with disease severity: moderate (420.2 ± 60.1) vs mild AL-PNP (307.2 ± 17.9; p = 0.0003) vs controls (207.0 ± 6.4; p < 0.0001). Proton spin density was also higher in moderate (tibial: 525.5 ± 53.0; peroneal: 553.6 ± 64.5; sural: 492.0 ± 56.6) and mild AL-PNP (tibial: 431.6 ± 22.0; peroneal: 457.6 ± 21.7; sural: 404.8 ± 25.2) vs controls (tibial: 310.5 ± 14.1; peroneal: 313.6 ± 11.6; sural: 261.7 ± 11.0; p < 0.0001 for all nerves). T2 relaxation time was elevated in moderate AL-PNP only (tibial: p = 0.0106; peroneal: p = 0.0070; sural: p = 0.0190). Tibial nerve caliber was higher in moderate (58.0 ± 8.8 mm 3 ) vs mild AL-PNP (46.5 ± 2.5 mm 3 ; p = 0.008) vs controls (39.1 ± 1.2 mm 3 ; p < 0.0001). Conclusions: MRN detects and quantifies peripheral nerve injury in AL-PNP in vivo with high sensitivity and in close correlation with the clinical stage. Quantitative parameters are feasible new imaging biomarkers for the detection of early AL-PNP and might help to monitor microstructural nerve tissue changes under treatment.